Treatment of an intraoral mandibular defect due to MRONJ, with an Integra dermal regeneration system and a vacuum formed splint. (8th October 2019) - Bradshaw, T.; Beech, A.; Farrier, S.; Spicer, K.; Farrier, J.
Abstract: Treatment of medication related osteonecrosis of the jaw with free‐flaps, leads to increased morbidity and scarring for patients. We present an alternative method of reconstruction post debridement, using a one stage dermal regeneration template system (Integra, Integra Life Sciences Corp, Plainsboro, NJ, USA) and acrylic splint to aid retention and healing.